Factors influencing cashless payment among Diploma in Muamalat students at UiTM Cawangan Selangor / Siti Hajar Mohd Senusi - Mohd Senusi, Siti Hajar (2019)
Nowadays, cashless payment has been accepted as a new method for transaction. This shows that community have awareness of the modern ways to pay. At the same time only a few numbers of youngster particularly students that use this type of payment. Cashless payment is the one of method to use to pay something in fast and secure process. Cashless payment is being introduced from the digital disruption, thanks to the introduction of cashless payment. In this study, the researcher aims to discuss the students‟ understanding about cashless payment and factors that influence Diploma in Muamalat students to use cashless payment. This study found that the majority of students know about cashless payment, had ever use cashless payment, and know that it is being accepted from Islamic perspectives. By using cashless payment, it can provide the fastest and easiest way to pay after purchasing something. The students must be more diligent to read news about economic or financial issues to follow the advance of technology. Therefore, this research was conducted by survey that had been distributed to the students WhatsApp.